2022
DOI: 10.2147/opth.s341698
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance of Extended Depth of Focus (EDOF) Intraocular Lenses – A Retrospective Comparative Study of Mini Well Ready and Symfony

Abstract: Purpose Extended depth of focus intraocular (EDOF) IOLs form a bridge between single- and multifocal IOL design. This study aimed to compare clinical outcomes obtained after implanting two different optical designs of EDOF IOLs: the Mini Well Ready (SIFI Medtech, Catania, Italy) and Tecnis Symfony (Abbott Laboratories, Illinois, USA). Methods The retrospective observational study included 61 patients (122 eyes) who underwent bilateral implantation of the Mini Well Ready… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The study carried out by Domínguez-Vicent et al demonstrated that MINI WELL is more defocus-tolerant for intermediate and near distances than TECNIS Symfony, in both photopic and scotopic conditions. This experimental result is consistent with the clinical outcomes, as reported by Nowik et al in their retrospective observational study [ 109 ]. Nowik et al compared MINI WELL with TECNIS Symfony from the clinical point of view; they found that MINI WELL provides a larger range of depth of focus than TECNIS Symfony, and the difference was statistically significant.…”
Section: Applicationssupporting
confidence: 92%
“…The study carried out by Domínguez-Vicent et al demonstrated that MINI WELL is more defocus-tolerant for intermediate and near distances than TECNIS Symfony, in both photopic and scotopic conditions. This experimental result is consistent with the clinical outcomes, as reported by Nowik et al in their retrospective observational study [ 109 ]. Nowik et al compared MINI WELL with TECNIS Symfony from the clinical point of view; they found that MINI WELL provides a larger range of depth of focus than TECNIS Symfony, and the difference was statistically significant.…”
Section: Applicationssupporting
confidence: 92%
“…The distance VA and the intermediate VA at 1-month follow-up appear consistent with the reports of other EDoF IOLs of different designs. [ 7 8 9 ] The range of good vision provided by RayOne EMV from far to 45 cm is also comparable to the standard designs available today. [ 5 ]…”
Section: Discussionmentioning
confidence: 86%
“…The results of our study using RayOne EMV match the results of Nowik et al, who have performed a similar study with EDoF IOLs of related design. [ 7 ] They noted that high spectacle independence for distance and near was found in eyes that had Technis Symfony and SIFI Mini Well Ready IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Good outcomes in terms of dysphotopsia are largely related to the modern nondiffractive X-wave technology, as many studies report that more undesirable dysphotopsia was experienced by patients with diffractive lenses. Nowik et al reported halo and glare phenomena in 40% and 3% of patients with a different model of non-diffractive Mini Well IOL implanted, respectively; worse outcomes were observed in patients with diffractive EDOF Symfony IOLs, with halo and glare occurring in 65.6% and 24% of patients, respectively [15]. It can be assumed that undesirable dysphotopic phenomena would be reduced if patients were asked about their occurrence over a period longer than 3 months.…”
Section: Discussionmentioning
confidence: 99%